Ultrasonographical morphology index in prediction of ovarian tumors malignancy - Szpurek, Dariusz; Uchman, Paweł; Moszyński, Rafał; Sajdak, Stefan (Contemporary Oncology/Współczesna Onkologia, 2001)
A morphology index based on six morphologic characteristics of ovarian tumors was developed using transvaginal ultrasonography. Tumor volume, wall structure, wall thickness, septal structure, echogenicity and ascites were analyzed. Examinations of 188 patients undergoing laparotomy for ovarian masses were evaluated using this index. The border value of the index was 7 points in distinguishing malignant from benign ovarian tumors. Morphological index created in this way was useful with a specificity of 93.6%, negative and positive predictive values of 97.4% and 61.1% respectively. It has a sensitivity of 80.1% and accuracy of 83.5%. These values, comparing to similar in other known morphological indices, are high. Using this morphological index allows a precision evaluation of ovarian tumor malignancy. It also makes possible taking proper decisions concerning ways of surgical treatment of ovarian tumors.